Exploring the Path to Enhance the Employment Guidance Ability of College Counselors in the New Era - Ding , Ziyue (Journal of Education and Educational Technologies, 2023)
With the continuous expansion of enrollment in universities, the number of college students graduating each year is increasing, and the employment situation for college students is becoming increasingly severe. Conducting employment guidance for college students is an important measure and means to enhance their employability and increase employment rates. College counselors are an important force in the employment guidance work of college students, and their ability to provide employment guidance is crucial. This article systematically elaborates on the current situation of counselor employment guidance work in the context of the new era, as well as the paths to improve counselor employment guidance ability. Although the relevant provisions of the administrative agreement in China are still in the new stage, although the theoretical field is developed late, in fact, there are relevant legal acts in practice. So far, the theoretical circle of our country has not reached a conclusion on the nature and system of administrative agreement, and has formed a unified view on the remedies of administrative agreement disputes. The special dual nature of administrative act provides a variety of possibilities for the study of its relief means.